Microvoids Evolution in S235JR Steel Subjected to Multi-Axial Stress State - KOSSAKOWSKI, Paweł Grzegorz; TRAMPCZYNSKI, Wiesław (Engineering Transactions, 2014)
The article presents the results of the experimental and numerical analysis of microvoids evolution in elements made of S235JR steel under multi-axial stress state. The numerical sim- ulations were based on the modified Gurson-Tvergaard-Needleman (GTN) material model, taking into account the impact of microstructural defects on the material strength. Two ap- proaches were used, assuming a global and local damage of the structure of S235JR steel. In both cases, the evolution of microdamage (voids) and their impact on the strength and failure of the material were analysed. The results of numerical simulations were similar to the results obtained during microstructural examinations.